Network analysis indicating the pharmacological mechanism of Yunpi-Qufeng-Chushi-prescription in prophylactic treatment of rheumatoid arthritis - Lin Li; Donghai Zhou; Qiuping Liu; Dianming Li; Qiao Wang; Xiaowei Shi; Chengping Wen; Lin Huang (BMC, 2021)
Abstract Background Rheumatoid arthritis (RA), is an autoimmune inflammatory disease with increasing global morbidity and high disability. Early treatment is an effective intervention to slow down joint deformation. However, as for early RA and pre-RA patients, it sometimes takes a long time to make a definite diagnosis and few guidelines have made suggestion for these suspected or early phrase individuals. Yunpi-Qufeng-Chushi-Prescription (YQCP) is an optimization of the traditional formula, Cangzhu Fangfeng Tang which is effective for arthromyodynia management. Methods In this study, LC-MS identify the main component of YQCP. Ingredients of the 11 herbs were collected from Traditional Chinese Medicine Integrated Database (TCMID). Targets of these ingredients were collected from two source, TCMID and PharmMapper. Microarray of 20 early untreated RA patients and corresponding health control were download from NCBI Gene Expression Omnibus (GEO) database to defined the differential expressed genes. Gene ontology analysis and KEGG enrichment analysis were carried out for the YQCP. Protein-protein interactions (PPIs) networks were constructed to identify the hub targets. At last, molecular docking (MD) were conducted to further verified the the possibility of YQCP for RA therapy. Result The study indicated that by acting on hub targets such as C3, EGFR, SRC and MMP9, YQCP may influence the mature of B cells and inhibit B cell-related IgG production, regulate oxidative stress and modulate activity of several enzymes including peroxidase and metallopeptidase to delay the occurrence and progress of RA and benefit the pre-RA or early RA patients. Conclusion YQCP is a potential effective therapy for prophylactic treatment of RA.